Empowering Communities through Participatory Educational Planning: A Review of Strategies and Outcomes - Sri Nurhayati; Pawwaz Najmi Izzatillah; Tiaranissa Anindita; Desi Silitonga; Ipin Sutisna; M. Zenal Muttaqin; Yayu Karimah; Rahma Nurhikmatussolihah; Eka Pelitawati; Neni Anggraeni; Rony Silalahi; Lim Fredy; Rita Sukarso; Zahrina Amalia; Yayang Siti Nurlia; Mochamad Ardioga (Jurnal Ilmiah Profesi Pendidikan, 2025)
Participatory planning in community-based education is increasingly recognized as a critical strategy to advance equity, learner agency, and context-sensitive program development. This study systematically synthesizes empirical and theoretical literature to examine how participatory planning is conceptualized, implemented, and evaluated in diverse community education contexts. Using a systematic literature review, 35 peer-reviewed articles published between 2000 and 2025 were analyzed from Scopus database. Studies were selected based on defined inclusion criteria, and key data were thematically reviewed to identify patterns in participatory strategies, enabling conditions, and educational outcomes. The findings reveal that participatory planning enhances curricular relevance, democratic governance, and social inclusion, especially when embedded in authentic and culturally responsive processes. It aligns educational practices with community priorities, strengthens stakeholder collaboration, and fosters long-term program sustainability. However, its effectiveness is often constrained by structural challenges, including institutional rigidity, uneven power dynamics, and limited facilitator capacity. The review highlights that the success of participatory planning is context-dependent and relational, requiring deliberate adaptation and sustained institutional support. This study advances an integrative framework linking forms of participation with educational impact and contributes a cross-contextual synthesis to the literature. It affirms the potential of participatory planning to democratize education and calls for further research into digital innovations, long-term outcomes, and governance-sensitive implementation.